Giant pseudocyst of the pancreas: A Case Report (One Health Journal of Nepal, 2021)
Pancreatic pseudocyst occurs as a common complication of pancreatitis and pancreatic trauma. Pseudocysts larger than 10 cm are termed giant pseudocysts and those more than 20cm are rarely encountered. Smaller pseudocysts may remain asymptomatic and resolve spontaneously. Giant pseudocysts may exert mass effect and the management can be challenging as both conservative and surgical approaches are associated with complications and recurrence. Endoscopic drainage is gaining popularity as the preferred treatment modality over surgical drainage, however, we opted for the latter due to the lack of expertise. We hereby present a case of giant pseudocyst drained surgically with an uncomplicated outcome.